Proximity: Localization vs. Distance in PR News Releases - Linda P. Morton; John Warren (Journalism & Mass Communication Quarterly, 1992)
Charting the use made of 197 news releases mailed from a Mississippi university to 121 daily and weekly state newspapers tested this question: which results in more use, the proximity of the public relations release source or localization of the facts in the story. The influence of proximity proved to be very slight but localization of stories resulted in relatively higher use. This study compared costs and concludes that localization of public relations news releases may be worth — in the age of word processing computers — the small extra expense.